Postural and gait symptoms in de novo Parkinson's disease patients correlate with cholinergic white matter pathology. (December 2021) - Nazmuddin, Muhammad; van Dalen, Jan-Willem; Borra, Ronald J.H.; Stormezand, Gilles N.; van der Horn, Harm Jan; van der Zee, Sygrid; Boertien, Jeffrey; van Laar, Teus
Abstract: Introduction: The postural instability gait difficulty motor subtype of patients with Parkinson's disease (PIGD-PD) has been associated with more severe cognitive pathology and a higher risk on dementia compared to the tremor-dominant subtype (TD-PD). Here, we investigated whether the microstructural integrity of the cholinergic projections from the nucleus basalis of Meynert (NBM) was different between these clinical subtypes. Methods: Diffusion-weighted imaging data of 98 newly-diagnosed unmedicated PD patients (44 TD-PD and 54 PIGD-PD subjects) and 10 healthy controls, were analysed using diffusion tensor imaging, focusing on the white matter tracts associated with cholinergic projections from the NBM (NBM-WM) as the tract-of-interest. Quantitative tract-based and voxel-based analyses were performed using FA and MD as the estimates of white matter integrity. Results: Voxel-based analyses indicated significantly lower FA in the frontal part of the medial and lateral NBM-WM tract of both hemispheres of PIGD-PD compared to TD-PD. Relative to healthy control, several clusters with significantly lower FA were observed in the frontolateral NBM-WM tract of both disease groups. Furthermore, significant correlations between the severity of the axial and gait impairment and NBM-WM FA and MD were found, which were partially mediated by NBM-WM state on subjects' attentional performance. Conclusions: The PIGD-PD subtype shows a loss of microstructural integrity of the NBM-WM tract, which suggests that a loss of cholinergic projections in this PD subtype already presents in de novo PD patients. Highlights: The integrity of the NBM-WM is lower in PIGD-PD. PIGD severity is associated with lower integrity of the NBM-WM. The lower integrity of NBM-WM in PIGD-PD suggests cholinergic pathology. DTI of NBM-WM may be used as a proxy of cholinergic dysfunction in PD patients.